2013
DOI: 10.1186/1471-244x-13-329
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of risk for anxiety-depression amongst Vietnamese-immigrants: a comparison with source and host populations

Abstract: BackgroundStudies suggest that immigrants have higher rates of anxiety-depression than compatriots in low-middle income countries and lower rates than populations in host high income countries. Elucidating the factors that underlie these stepwise variations in prevalence may throw new light on the pathogenesis of anxiety-depressive disorders globally. This study aimed to examine whether quantitative differences in exposure to, or the interaction between, risk factors account for these anxiety-depression preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
(63 reference statements)
1
14
0
Order By: Relevance
“…Regarding the factor age , most studies on other migrant populations have revealed a mental health advantage for younger ( 45 ) and disadvantage for older ( 46 ) migrants while the middle-aged frequently appear relatively unaffected. Therefore, concerning our Vietnamese sample, it cannot be entirely determined if age indeed was not a mental health key factor or if it has merely not unfolded its full effect since our participants were, on average, 45 years old and thus not part of any risk group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the factor age , most studies on other migrant populations have revealed a mental health advantage for younger ( 45 ) and disadvantage for older ( 46 ) migrants while the middle-aged frequently appear relatively unaffected. Therefore, concerning our Vietnamese sample, it cannot be entirely determined if age indeed was not a mental health key factor or if it has merely not unfolded its full effect since our participants were, on average, 45 years old and thus not part of any risk group.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, concerning our Vietnamese sample, it cannot be entirely determined if age indeed was not a mental health key factor or if it has merely not unfolded its full effect since our participants were, on average, 45 years old and thus not part of any risk group. Regarding the factor gender , several studies have revealed a heightened mental health risk for female Vietnamese ( 45 ). However, some studies on other migrant populations have reported the opposite; for example, increased PTSD rates among male migrants in Finland ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood of MHC utilization is significantly correlated with perceived needs (e.g., anxiety, depression, substance abuse; S.-L. L. Williams, 2014). Some previous studies suggested that because of the immigration experience, foreign-born adults face more mental stressors and problems compared to the U.S.-born population (Leong & Lau, 2001), including anxiety (Liddell et al, 2013), depression (Antoniades, Mazza, & Brijnath, 2014), posttraumatic stress disorder (Eisenbruch, 1991), substance abuse (De La Rosa, Babino, Rosario, Martinez, & Aijaz, 2012), and other severe mental illnesses (Saechao et al, 2012;David T. Takeuchi, Akgría, Jackson, & Williams, 2007).…”
Section: Needs Of Mhp Visitingmentioning
confidence: 99%
“…[ 14 15 ] Certain demographic and psychosocial risk factors for anxiety-depression appear to be universal, in particular,[ 16 17 18 19 ] female gender;[ 16 ] unemployment;[ 17 ] lower levels of education;[ 18 ] young (vs. older) adulthood;[ 19 ] co-morbid substance use disorder (SUD);[ 20 ] physical ill-health;[ 21 ] and exposure to potentially traumatic events or postpartum depression. [ 22 23 ]…”
Section: Introductionmentioning
confidence: 99%